Validation of the Turkish Version of the Parents’ Evaluation of the Aural/Oral Performance of Children (PEACH) Rating Scale - Eroğlu, Kader; İpek Şahin Kamışli, Gurbe; Altınyay, Şenay; Gökdoğan, Çağıl; Bayramoğlu, İsmet; Kemaloğlu, Yusuf K. (ENT Updates, 2021)
Background: The Parents’ Evaluation of the Aural/Oral Performance of Children (PEACH) Rating Scale is a widely used instrument to evaluate adaptation, effectiveness of hearing aid and cochlear implant, and auditory rehabilitation outcomes in hearing-impaired children by parent observation in daily life listening situations. This study aimed to adapt the Parents’ Evaluation of the Aural/Oral Performance of Children to Turkish children, analyze, and verify the validity and the reliability. We also looked for scores in various clinical conditions (age, sex, HA, CI experience, unilateral vs. bilateral users). Methods: The study composed of 120 children with hearing loss (hearing aid users n = 57; cochlear implant users n = 63) between 3 and 12 (mean: 7.51±2.84) years of age. First, Parents’ Evaluation of the Aural/Oral Performance of Children was adapted to Turkish children, and confirmatory factor analysis was used to evaluate the validity of the Turkish Parents’ Evaluation of the Aural/Oral Performance of Children. Then, correlations of Turkish Parents’ Evaluation of the Aural/Oral Performance of Children scores with age, hearing aid and cochlear implant experience, and group differences (male vs. female; hearing aid vs. cochlear implant users) were analyzed by using the proper statistical tests. Cronbach’s alpha coefficient was used to confirm internal consistency, and the test-retest method was performed to evaluate the reliability of the measurement. Results: Turkish Parents’ Evaluation of the Aural/Oral Performance of Children has high internal consistency (Cronbach's alpha = 0.942) and test-retest reliability (r = 0.949, P < .001). Scores were increased in parallel to age, hearing aid, cochlear implant experience, and there was a significant difference in Turkish Parents’ Evaluation of the Aural/Oral Performance of Children scores between unilateral and bilateral cochlear implant users. Conclusion: The Turkish Parents’ Evaluation of the Aural/Oral Performance of Children could be recommended as a convenient tool for children with hearing aid and cochlear implant to monitor functional, auditory, and communication skills.